Model Layanan Konseling di Pesantren - Ainy Rambe, Syarifah; Ayu Mahara, Rezeki; Maulida, Fitri (Jumper: Journal of Educational Multidisciplinary Research, 2024)
Guidance and counseling is an effort carried out in the process of alleviating student problems, one of which is learning problems. The guidance counseling process can be carried out with several services. In public schools, there are several models of counseling services that are implemented, such as group services, consultation services, information services, behavioral counseling services, and others. The aim of this research is to find out what models of counseling services are implemented in Islamic boarding schools for students. The method used is Systematic Literature Review (SLR), which is a way of identifying, evaluating and interpreting all available research that is relevant to the problem formulation or topic area under study. Research results show that in Islamic boarding schools there are four models of counseling services implemented, the four services include group counseling services, classical guidance services, individual counseling services, model fan counseling